Social Capital, Subjective Norm, Product Knowledge, Environmental Concern, and Perceived Behavioral Control on Purchase Intensity of Recycled Products in MSMEs - Doli Muhammad Jafar Dalimunthe; Tengku Ezni Balqiah; Heri Pratikto; Rifelly Dewi Astuti; Arif Qaedi Hutagalung (TALENTA Publisher, Universitas Sumatera Utara, 2026)
This study aims to examine the effect of social capital, subjective norms, product knowledge, environmental concern, and perceived behavioral control on purchase intensity of recycled products in MSMEs in Indonesia. A total of 530 respondents were selected from North Sumatra, West Java, and East Java using purposive sampling. The data were analyzed using Partial Least Square (PLS)-based Structural Equation Modeling (SEM). The results show that environmental concern, perceived behavioral control, and subjective norms have a significant effect on purchase intensity. Furthermore, subjective norms mediate the relationship between social capital and perceived behavioral control on purchase intensity. This study provides insights into consumer behavior toward environmentally friendly products and supports the development of sustainable MSMEs.